A Quality Improvement Initiative to Decrease Central Line–Associated Bloodstream Infections During the COVID-19 Pandemic: A "Zero Harm" Approach. Issue 3 (24th April 2023) - Redstone, Carol S.; Zadeh, Maryam; Wilson, Mary-Agnes; McLachlan, Samantha; Chen, Danny; Sinno, Maya; Khamis, Safiyya; Malis, Kassia; Lui, Flavia; Forani, Steven; Scerbo, Christina; Hutton, Yuka; et al.
Abstract : Introduction: Central line–associated bloodstream infections (CLABSIs) are associated with significant patient harm and health care costs. Central line–associated bloodstream infections are preventable through quality improvement initiatives. The COVID-19 pandemic has caused many challenges to these initiatives. Our community health system in Ontario, Canada, had a baseline rate of 4.62 per 1000 line days during the baseline period. Objectives: Our aim was to reduce CLABSIs by 25% by 2023. Methods: An interprofessional quality aim committee performed a root cause analysis to identify areas for improvement. Change ideas included improving governance and accountability, education and training, standardizing insertion and maintenance processes, updating equipment, improving data and reporting, and creating a culture of safety. Interventions occurred over 4 Plan-Do-Study-Act cycles. The outcome was CLABSI rate per 1000 central lines: process measures were rate of central line insertion checklists used and central line capped lumens used, and balancing measure was the number of CLABSI readmissions to the critical care unit within 30 days. Results: Central line–associated bloodstream infections decreased over 4 Plan-Do-Study-Act cycles from a baseline rate of 4.62 (July 2019–February 2020) to 2.34 (December 2021–May 2022) per 1000 line days (51%). The rate of central line insertion checklists used increased from 22.8% to 56.9%, and central line capped lumens used increased from 72% to 94.3%. Mean CLABSI readmissions within 30 days decreased from 1.49 to 0.1798. Conclusions: Our multidisciplinary quality improvement interventions reduced CLABSIs by 51% across a health system during the COVID-19 pandemic.